Mixed Finite Element for Crack Analysis in Functionally Graded Material - Benmalek, Haroune; Bouziane, Salah; Bouzerd1, Hamoudi; Remmani, Sid Ahmed (International Journal of Sustainable Construction Engineering and Technology, 2023)
This study presents a mixed finite element formulated using isoparametric techniques and extended to analyze quasi-static crack propagation in functionally graded materials. The mixed mode is analyzed for homogeneous and functionally graded beams subjected to three-point bending and for homogeneous and functionally graded plates under uniform axial tension. The mixed finite element results are compared with previous experimental and numerical results published in the literature.